A PROSPECTIVE OBSERVATIONAL STUDY ON COMPARISON OF COMPUTED TOMOGRAPHY AND ULTRASOUND IN EVALUATION OF ACUTE ABDOMEN AMONG ADULTS - Sharan, Ashutosh; Sharan, Nikita; Sharan, Nikhil (Student's Journal of Health Research Africa, 2023)
Background: In order to reduce radiation exposure, the goal of this study was to examine the roles of computed tomography and ultrasound in the evaluation of acute abdomen. It also sought to determine whether ultrasound alone would be sufficient in most cases. Method: For non-traumatic acute abdominal discomfort that lasted less than three days, 50 adult patients visited the emergency room. This prospective observational study was authorized by the institutional review board. The surgery department of Sharan Nursing Home, Motihari, Bihar performed the radiological evaluation of the abdomen using ultrasonography and CT scans (both non-contrast and contrast-enhanced). Trauma and being pregnant were the exclusion factors. Results: There was no statistically significant difference between the overall sensitivity of the ultrasound and the CT (p = 0.018). Additionally, there were no appreciable differences between the sensitivity of ultrasound and CT in diagnosing frequent causes of acute abdomen, such as acute cholecystitis, acute appendicitis, intestinal obstruction, pancreatitis, and ureteric calculi. Only patients with retro-caecal appendicitis, cases of intestinal blockage where the transition point needed to be defined, and patients with pancreatitis where the CT Severity index needed to be obtained were candidates for CT. Conclusion: Considering that ultrasound has been shown to have a sensitivity that is comparable to CT in the majority of clinical scenarios, we conclude that ultrasound should continue to be the primary imaging modality in all patients with acute abdomen in order to prevent radiation exposure. It is also a more economical inquiry. As a result, CT should only be used in a small number of clinical circumstances where ultrasound is severely inconclusive. Recommendation: Both CT and ultrasonography tests must be conducted in order to ensure a certain conclusion in acute abdomen cases.